Styrene stereospecific catalysis by alkyl substituted titanocenes of the type (RCp)(2)TiCl2 - Pereira, BCD (2000)
A series of seven alkyl substituted complexes of the type (RCp)(2) TiCl2 (R =H, ethyl, n-propyl, iso-propyl, n=butyl, iso-amyl, ciclo-hexyl) was prepared, as well as the novel compound with R = sec-butyl, and the effects of the substituent on the polymerisation of styrene was investigated at the temperatures of 0 and 50 degreesC. It was found that R = n=butyl maximises the production of syndiotactic polystyrene. Alkyl ligands with R = RCH2- are superior to those with R = RR'CH- and to the precursor Cp2TiCl2 in the production of high molecular weight syndiotactic polystyrene.